1982
DOI: 10.1080/01904168209363061
|View full text |Cite
|
Sign up to set email alerts
|

Transport of iron into leaves following iron resupply to iron‐stressed sugar beet plants

Abstract: Iron-stressed sugar beets were resupplied with ferrous salts and ferric EDTA and the transport of iron into leaves was monitored with time. After 24 hours of iron resupply, leaf iron concentrations increased 11-fold whether iron was resupplied as ferrous sulfate or ferric EDTA. There was a substantial increase in leaf iron during the first two hours with the maximum rate of accumulation occurring during the first six hours after resupply began. The massive transport of iron into leaves following iron resupply … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 16 publications
2
8
0
Order By: Relevance
“…Although changes in Fe uptake are correlated with changes in reductase activity, the question as to whether the increase in uptake rates is because of enhanced transporter activity, a consequence of increased reduction capacity, or both, is difficult to answer and experiments addressed to this issue have yielded somewhat conflicting data. Young & Terry (1982) showed that Fe deficiency induced an increase in both uptake rates and leaf concentration of Fe when Fe was supplied as Fe# + via the nutrient solution, pointing to enhanced activity of a plasmalemma Fe# + -transport protein. By contrast, Grusak et al (1990a) found similar ratios of Fe# + absorbed : Fe() reduced in Fe-replete and Fe-deficient pea roots.…”
Section: Iron Uptakementioning
confidence: 99%
“…Although changes in Fe uptake are correlated with changes in reductase activity, the question as to whether the increase in uptake rates is because of enhanced transporter activity, a consequence of increased reduction capacity, or both, is difficult to answer and experiments addressed to this issue have yielded somewhat conflicting data. Young & Terry (1982) showed that Fe deficiency induced an increase in both uptake rates and leaf concentration of Fe when Fe was supplied as Fe# + via the nutrient solution, pointing to enhanced activity of a plasmalemma Fe# + -transport protein. By contrast, Grusak et al (1990a) found similar ratios of Fe# + absorbed : Fe() reduced in Fe-replete and Fe-deficient pea roots.…”
Section: Iron Uptakementioning
confidence: 99%
“…Next, addition of excess iron in the culture medium of iron-starved plantlets leads to a large iron influx into the plant [53]. This iron is translocated within 3 h into the leaves to restore the essential photosynthetic process in chloroplasts [57,58]. During this period of regreening, which takes about 24-48 h, ferritins are used as a safe iron buffer and transiently store the iron required for the synthesis of iron-containing proteins.…”
Section: Iron-dependent Regulation Of Ferritin Gene Expressionmentioning
confidence: 99%
“…Seeds were germinated and grown in vermiculite for two weeks. Seedlings were grown for two more weeks in nutrient solution (in 3/8-strength Hoagland's nutrient solution with 22.4 laM Fe and then transplanted (four plants per bucket) to 20-1 plastic buckets lined with polyethylene bags and containing half-strength Hoagland's solution (Young and Terry 1982) with either 0 or 44.8 I~M Fe. Iron was added in the chelated form of Fe-EDDHA (Sequestrene 138; Ciba-Geigy, Barcelona, Spain).…”
Section: Plant Culture Sugar Beet (Beta Vulgaris L Monohil Hybrid;mentioning
confidence: 99%